Innovating real-time item analysis of assessment for competency-based biostatistics education using X-DAS cloud system - Ibrahim, Mohd Salami; Abu Bakar, Yasrul Izad; Abdul Ghani, Azril Shahreez; Ahmad, Anisa (UKM Press, 2024)
Introduction: Learning analytics and timely feedback are essentials for competency attainment. In response, we developed the copyrighted X-DAS system using Microsoft 365 cloud tools (Forms, OneDrive, SharePoint, Power Automate, and Excel Online 365) to deliver real-time item analysis in undergraduate biostatistics courses for medical sciences degree (BMHS) and nursing degree (NSD). X-DAS tracks attendance and provides immediate insights into the difficulty index, discrimination index, and distractor analysis of one-best answer (OBA) assessments, presented through Business-Intelligence (BI) dashboards. This study evaluates the effectiveness of this innovation. Method: Two student groups, BMHS (n=58) and NSD (n=21), completed a 30-question OBA pre-test (30 minutes) and a post-test (15 minutes) to assess both competency and fluency. BI dashboards provided visual feedback on how students and their peers answered each question, enabling lecturers to identify strong distractors, challenging items, and highquality questions for future high-stakes exams. The post-test contributed to continuous assessment grades for NSD but remained formative for BMHS. A repeated measures ANOVA with mixed models evaluated pre- and post-test differences and group interactions. Results: All assumptions for repeated measures ANOVA were met. Pre-test scores showed no significant difference between BMHS (M = 18.4, SD = 4.9) and NSD (M = 19.6, SD = 5.4; P= 0.180). Post-test scores did not differ significantly between groups (BMHS: M = 28.1, SD = 4.2; NSD: M = 28.8, SD = 3.9; P = 0.112). Both groups significantly improved from pre-test to post-test (P < 0.001). Interaction effects indicated no significant difference in score gains between BMHS and NSD (P = 0.544), demonstrating comparable improvement in scores. Conclusion: Real-time analytics with BI dashboards significantly enhance competency in biostatistics education by providing actionable insights for students and lecturers. The innovation offers rejuvenated technology-enhanced assessment and teaching for broader fields of study.